Olive leaf extract inhibits metastatic melanoma spread through suppression of epithelial to mesenchymal transition. (10th August 2022) - De Cicco, Paola; Ercolano, Giuseppe; Tenore, Gian Carlo; Ianaro, Angela
Abstract: Olive tree leaves are an abundant source of bioactive compounds with several beneficial effects for human health, including a protective role against many types of cancer. In this study, we investigated the effect of an extract, obtained from olive tree (Olea europaea L.) leaves (OLE), on proliferation, invasion, and epithelial to mesenchymal transition (EMT) on metastatic melanoma, the highly aggressive form of skin cancer and the deadliest diseases. Our results demonstrated that OLE inhibited melanoma cells proliferation through cell cycle arrest and induction of apoptotic cell death. Moreover, OLE suppressed the migration, invasion, and colonies formation of human melanoma cells. Similar to our in vitro findings, we demonstrated that the oral administration of OLE inhibited cutaneous tumor growth and lung metastasis formation in vivo by modulating the expression of EMT related factors. In addition, the anti‐proliferative and anti‐invasive effects of OLE against melanoma were also related to a simultaneous targeting of mitogen‐activated protein kinase and PI3K pathways, both in vitro and in vivo. In conclusion, our findings suggest that OLE has the potential to inhibit the metastatic spread of melanoma cells thanks to its multifaceted mechanistic effects, and may represent a new add‐on therapy for the management of metastatic melanoma.